Inclusion and Convolution Properties of a Certain Class of Analytic Functions - Al-Kaseasbeh, Mohammad; Darus, Maslina (Eurasian Mathematical Journal, 2017)
In this article, the class \( \mathcal{R}^n(λ, α, β, γ, δ) \) of analytic functions defined by using the combination of generalised operators of Salagean and Ruscheweyh is introduced. Inclusion relations, convolution properties and other properties for the class \( \mathcal{R}^n(λ, α, β, γ, δ) \) are given.